Futuros desenvolvimentos na instrumentação em fluorofotometria ocular. - E B Leite; J G Cunha-Vaz (Acta Médica Portuguesa, 1992)
The scope of ocular fluorometry is to monitor exogenous and endogenous fluorophores in ocular tissues, in relation with ophthalmic and systemic diseases using the unique optical prospectives of the eye. The elderly population and the incidence of blindness are increasing rapidly due to more cases of diabetes, glaucoma, cataract and age-related macular degeneration. Monitoring changes in specific fluorophores in the eye may help identify the high risk groups in these diseases. New developments in instrumentation include differential fluorometry and introduction of confocal optics. Differential fluorometry has already achieved significant progress for the study of the autofluorescence of the lens and cornea and measurements in the aqueous. Improved spatial resolution obtained with improved optics opens interesting possibilities like measurement of corneal endothelial permeability and retinal vascular permeability. The results already obtained will be presented with particular incidence on measurements of lens fluorescence (normals--336.2 +/- 56.3; diabetes--659.9 +/- 123.9; age group--40-50 y) and corneal endothelial permeability (normals--3.14 +/- 60.10(-1) cm-1).